An Evaluation of Determining the Critical Success Factors for Implementing Total Quality Management - Islam, Md. Shajedul (Asian Accounting and Auditing Advancement, 2017)
Many organizations have looked upon total quality management (TQM) as a way by which they could maintain a competitive edge, in recent years. Thus, this study attempted to identify the critical success factors of TQM implementation. Furthermore, this study has reviewed much-related literature which is relevant to critical success factors of TQM and its implementation in various organizations. The review focuses on the implementations, the impacts on the organization’s performance, and the encouraging indicators to adopt TQM in the organization. This study concludes on the critical success factors of TQM implementation. Because of the lack of identifying reasons, many organizations do not adopt the TQM approach properly into their organization. However, some organizations have already identified the benefits of the implementation of TQM on their organizational performance and they believe this approach could give them a chance to achieve their goals.